Artificial Intelligence’s Expanding Role in Healthcare Administration: A Technological Revolution or a Risky Disruption? - Durusoy, Okan (Technium Social Sciences Journal, 2025)
The power of Artificial intelligence (AI) can be harnessed to transform healthcare administration into a more efficient and cost-effective system that drives improved patient outcomes. In this review, we examine the broader role of AI in healthcare within the contours of healthcare systems, with specific emphasis on the current use of AI in data, predictive analytics, and decision support. The paper provides a critical appraisal of the opportunities and challenges of integrating AI, from data privacy and algorithmic fairness to over-dependence upon technology. It also delves into the moral and regulatory grey area that these healthcare administrators must navigate as AI technology becomes further integrated into institutional structures. Focusing on the strategic leadership, multidisciplinary cooperation and organizational readiness, this study highlights that a successful implementation of AI requires not only investments in technology but also a whole strategic design and ethical anticipation. The review is outlined and as well as the current trends and up-and-coming areas is presented and the continuous medical education and updating of the healthcare professionals are emphasized. At its core, this study aims to provide policymakers with a better understanding of how they can best embrace AI’s game-changing potential in a way that minimizes the risks, providing as a counterweight to guide healthcare institutions as they navigate this rapidly evolving technological landscape.